Researching Children’s Multiple Family Relations: Social Network Maps and Life-Lines as Methods - Pirskanen, Henna; Jokinen, Kimmo; Kallinen, Kati; Harju-Veijola, Minna; Rautakorpi, Sonja (Qualitative Sociology Review, 2015)
Visual methods are reported to have certain advantages when conducting interviews on sensitive topics, such as intimate spaces, home-related ethical issues, and vulnerable families. In this article, we concentrate on two visual methods: social network maps and life-lines. In our research project on children’s well-being and emotional security in multiple family relations, we collected data by interviewing children and asking them to complete social network maps and life-lines. We discuss the suitability of these two visual methods for describing children’s close relationships with their family members and significant others. Combining these two methods during an interview process with children has not very often been tested. It is thus argued that these particular methods help a child to explain his or her family relations and life events. For the researcher interested in studying challenging and complex family relations, they can be extremely useful tools.